Diagnostic accuracy of nasal nitric oxide for establishing diagnosis of primary ciliary dyskinesia: a meta-analysis - Kouis, Panayiotis; Papatheodorou, Stefania; Yiallouros, Panayiotis K. (My University, 2015)
Background: To date, diagnosis of Primary Ciliary Dyskinesia (PCD) remains difficult and challenging. We systematically evaluated the diagnostic performance of nasal Nitric Oxide (nNO) measurement for the detection of PCD, using either velum-closure (VC) or non-velum-closure (non-VC) techniques. Methods: All major electronic databases were searched from inception until March 2015 using appropriate terms. The sensitivity and specificity of nNO measurement was calculated in PCD patients diagnosed by transmission electron microscopy, high speed video-microscopy or genetic testing. Summary receiver operating characteristic (HSROC) curves were drawn using the parameters of the fitted models. Results: Twelve studies provided data for 13 different populations, including nine case-control (n=793) and four prospective cohorts (n=392). The overall sensitivity of nNO measured by VC techniques was 0.95 (95% CI 0.91-0.97), while specificity was 0.94 (95% CI 0.88-0.97). The positive likelihood ratio (LR+) of the test was 15.8 (95% CI 8.1-30.6), whereas the negative likelihood ratio (LR-) was 0.06 (95% CI 0.04-0.09). For non-VC techniques, the overall sensitivity of nNO measurement was 0.93 (95% CI 0.89-0.96) whereas specificity was 0.95 (95% CI 0.82-0.99). The LR+ of the test was 18.5 (95% CI 4.6-73.8) whereas the LR- was 0.07 (95% CI 0.04-0.12). Conclusions: Diagnostic accuracy of nNO measurement both with VC and non-VC maneuvers is high and can be effectively employed in the clinical setting to detect PCD even in young children, thus potentiating early diagnosis. Measurement of nNO merits to be part of a revised diagnostic algorithm with the most efficacious combination of tests to achieve PCD diagnosis.
Keywords: Diagnosis; Kartagener syndrome; Nitric oxide; Primary ciliary dyskinesia